Hormesis effects in tomato plant growth and photosynthesis due to acephate exposure based on physiology and transcriptomic analysis. Issue 6 (7th February 2023) - Xu, Nuo; Sun, Yang; Wang, Yuru; Cui, Yidi; Jiang, Yuanjin; Zhang, Chao
Abstract: BACKGROUND: Hormesis is a common phenomenon in toxicology described as low‐dose stimulation due to a toxin which causes inhibition at a high dose. Pesticide hormesis in plants has attracted considerable research interest in recent years; however, the specific mechanism has not yet been clarified. Acephate is an organophosphorus insecticide that is used worldwide. Here, hormesis in tomato ( Solanum lycopersicum L.) plant growth and photosynthesis after acephate exposure is confirmed, as stimulation occurred at low stress levels, whereas inhibition occurred after exposure to high concentrations. RESULTS: We found that low acephate concentration (5‐fold lower than recommended application dosage) could enhance chlorophyll biosynthesis and stimulate photosynthesis effects, and thus improve S. lycopersicum growth. A high level of acephate (5‐fold higher than recommended application dosage) stress inhibited chlorophyll accumulation, decreased photosystem II efficiency and blocked antioxidant reactions in leaves, increasing reactive oxygen species levels and damaging plant growth. Transcriptomic analysis and quantitative real‐time PCR results revealed that the photosynthesis – antenna proteins pathway played a crucial role in the hormesis effect, and that LHCB7 as well as LHCP from the pathway were the most sensitive to acephate hormesis. CONCLUSION: Our results showed that acephate could induce hormesis in tomato plant growth and photosynthesis, and that photosystem II and the photosynthesis – antenna proteins pathway played important roles in hormesis. These results provide novel insights into the scientific and safe application of chemical pesticides, and new guidance for investigation into utilizing pesticide hormesis in agriculture. © 2023 Society of Chemical Industry. Abstract : Acephate at low concentrations could enhance chlorophylls biosynthesis and promote photosynthesis, improving plant growth, while high levels of acephate would block antioxidant reaction, increasing ROS levels and damaging plant growth. Photosystem II and photosynthesis – antenna proteins pathway played a crucial role in acephate hormesis.